(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Erlangga, Effendi H, Damar A, Taryono, Nurjaya IW. 2025. Phytoplankton diversity as a bioindicator of organic pollution in the estuary of Lhokseumawe City, Aceh, Indonesia. Biodiversitas 26: 3528-3544. Phytoplankton biodiversity serves as a crucial bioindicator of organic pollution in estuarine ecosystems. This study aims to assess phytoplankton diversity in the Lhokseumawe Estuary, Aceh Province, Indonesia, to evaluate organic pollution levels. Sampling was conducted at five stations from July to November 2024 using a purposive sampling method. Phytoplankton were identified and analyzed to determine species composition, abundance, and ecological indices. A total of 32 species from five major phytoplankton classes were identified, dominated by Bacillariophyceae (43%) and Mediophyceae, while Cyanophyceae contributed only 3%. The highest species richness was observed in July (25 taxa), decreasing to 20 taxa in September. Phytoplankton abundance declined from 20,525,346 cells/m³ in July to 13,609,643 cells/m³ in November. Spatially, the highest phytoplankton abundance occurred at stations 5 and 3, indicating localized nutrient inputs from surrounding anthropogenic sources. The Mediophyceae class exhibited the highest abundance, while Dinophyceae had the lowest. The Shannon diversity index (H’) ranged from 1.79 to 2.30 and evenness from 0.65 to 0.77, indicating moderate community stability with low dominance (0.14-0.24) across stations. The prevalence of Bacillariophyceae and Mediophyceae, particularly eutrophication-tolerant genera like Nitzschia, Navicula, Skeletonema, and Chaetoceros, suggests nutrient enrichment from anthropogenic sources such as domestic wastewater and agricultural runoff. However, the low Palmer Pollution Index score (6) and Algae Group Index value (3.61) indicate that organic pollution remains minimal, with diatom dominance reflecting relatively good water quality conditions. Seasonal variations in abundance and composition further highlight the influence of environmental changes and pollution on estuarine phytoplankton dynamics. These findings confirm that the Lhokseumawe Estuary is experiencing eutrophication driven by organic pollution, and the phytoplankton biodiversity metrics provide reliable indicators for monitoring such environmental disturbances. This study represents the first assessment of phytoplankton diversity in this region and provides essential baseline data for ongoing environmental monitoring and management strategies.